Asphalt-based hard carbon material for sodium-ion battery negative electrode and preparation method thereof
Patent Information
- Application Number
- CN202611197968.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-16
AI Technical Summary
例如,CN115259134B采用离子交换树脂与沥青进行熔融共混实现共熔交联,阻断芳香分子的平行滑动与重排,从而抑制软碳化趋势;然而,树脂与沥青仅为物理共混,交联效率较低且均匀性不足,难以实现分子级别的精准调控
[0022]本发明以含氧杂环的二酰卤化合物为交联剂,在路易斯酸的催化作用下,通过傅克反应与沥青分子发生分子级精准交联,形成刚性交联网络,从而抑制芳香层片在高温下的熔融重排;同时利用含氧基团与路易斯酸中的金属离子的配位作用实现了金属离子在沥青基体中的分子级锚定,经预炭化和高温炭化后原位形成大量纳米级闭孔,并同步实现氧掺杂。在交联、造孔与掺杂的协同作用下,制得具有高度无序碳结构、大层间距及丰富闭孔特征的硬碳材料,其储钠容量和首次库伦效率均得到提升,且倍率性能优异。
Smart Images

Figure CN122916104A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to an asphalt-based hard carbon material for the negative electrode of a sodium-ion battery and its preparation method. Background Technology
[0002] With the rapid development of the global large-scale energy storage and electric vehicle markets, sodium-ion batteries have become highly competitive energy storage devices after lithium-ion batteries due to their advantages such as abundant sodium resources and low cost. In sodium-ion battery systems, the cathode material is relatively mature, while the anode material has become one of the key factors restricting its commercialization. The large radius of sodium ions (1.02 Å) makes it difficult for traditional graphite anodes to effectively intercalate sodium ions. Therefore, hard carbon materials with highly disordered microstructures, large interlayer spacing, and abundant closed pores have become the core research direction for sodium-ion battery anodes. Asphalt, due to its low price, abundant resources, and high residual carbon content, is an ideal precursor for preparing hard carbon materials. However, the carbon materials obtained after direct calcination of asphalt have high order and low closed-pore ratio, resulting in insufficient sodium storage capacity in the low-potential plateau region. The fundamental reason is that the polycyclic aromatic hydrocarbon components in asphalt are prone to melt rearrangement during pyrolysis, stacking parallel under π-π forces, and gradually transforming into graphitized microcrystals with narrow interlayer spacing and dense structure as the temperature rises, which is not conducive to the interlayer diffusion and pore storage of sodium ions.
[0003] To suppress the graphitization tendency of asphalt, researchers typically employ strategies such as molecular crosslinking, template pore creation, and heteroatom doping to pretreat the precursor. By constructing a rigid crosslinking network during the pretreatment stage, the directional sliding and melt rearrangement of aromatic lamellars are suppressed, resulting in hard carbon materials with sodium storage activity after high-temperature calcination. For example, CN115259134B uses ion exchange resin and asphalt for melt blending to achieve co-melt crosslinking, blocking the parallel sliding and rearrangement of aromatic molecules, thereby suppressing the soft carbonization trend. However, the resin and asphalt are only physically blended, resulting in low crosslinking efficiency and insufficient uniformity, making precise molecular-level control difficult. CN115991467A modifies asphalt through gas-phase oxidation for crosslinking; however, the degree of crosslinking in gas-phase oxidation is difficult to control precisely, and excessive oxidation can easily lead to precursor structural collapse or uneven crosslinking. CN116354335A utilizes a crosslinking agent to achieve chemical crosslinking of asphalt under solvothermal conditions; however, the crosslinking agent used has limited reactivity with asphalt molecules, resulting in insufficient crosslinking network strength. CN119038529B employs a phosphorus-sulfur co-doping strategy. By introducing specific modified crosslinking agents, composite pore-forming agents, and phosphorus and sulfur sources into carbon source precursors such as anthracite, while crosslinking locks the sliding of the carbon layer, large-radius heteroatoms (such as P and S) are squeezed into the carbon lattice to forcibly widen the interlayer spacing, thereby synergistically improving the sodium storage capacity of the slope and plateau regions.
[0004] While the aforementioned methods can suppress the graphitization tendency of asphalt to some extent, they still suffer from problems such as low crosslinking efficiency, poor uniformity, or independent crosslinking and doping processes lacking synergistic design. This results in uneven pore distribution, low closed-cell rate, and limited interlayer spacing control, making it difficult to further improve sodium storage capacity. Therefore, there is an urgent need to develop a method for preparing asphalt-based hard carbon materials that can achieve precise molecular-level crosslinking, in-situ pore formation, and uniform doping in a synergistic manner to solve the problems of low closed-cell rate, small interlayer spacing, and insufficient sodium storage capacity in existing technologies. Summary of the Invention
[0005] The present invention aims to perform precise molecular-level crosslinking of asphalt and synergistically achieve in-situ pore formation and uniform doping to reduce the orderliness of hard carbon materials, increase the closed-pore rate, and thus improve electrochemical performance.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A method for preparing an asphalt-based hard carbon material for a sodium-ion battery negative electrode includes the following steps:
[0008] S1. Add asphalt powder, oxygen-containing heterocyclic diacyl halide compound, and Lewis acid to an organic solvent, and then stir to react to obtain modified asphalt;
[0009] S2. Modified asphalt is pre-carbonized and then carbonized at high temperature under an inert atmosphere to obtain asphalt-based hard carbon material for sodium-ion battery anodes.
[0010] Further, in step S1, the mass ratio of the asphalt powder, the oxygen-containing heterocyclic diacyl halide compound, and the Lewis acid is 100:(5~10):(8~12), preferably 100:(5~8):(8~10).
[0011] Furthermore, in step S1, the asphalt powder is selected from at least one of coal tar pitch, petroleum asphalt, shale asphalt, natural asphalt, and mesophase asphalt, with a softening point of 65-160℃ and a particle size of 200-400 mesh. Asphalt with a suitable particle size ensures a more uniform reaction process and more complete modification in the subsequent process.
[0012] Further, in step S1, the oxygen-containing heterocyclic diacyl halide compound is selected from at least one of 2,5-furandicarboxylic acid chloride and 4H-pyran-2,6-dicarboxylic acid chloride, preferably 2,5-furandicarboxylic acid chloride.
[0013] Further, in step S1, the Lewis acid is selected from at least one of aluminum chloride (AlCl3), zinc chloride (ZnCl2), magnesium chloride (MgCl2), and ferric chloride (FeCl3); preferably zinc chloride (ZnCl2).
[0014] Further, in step S1, the solvent is selected from at least one of tetrahydrofuran, N-methylpyrrolidone, carbon tetrachloride, dichloroethane, and n-heptane.
[0015] Preferably, in step S1, the reaction raw materials also include pyromellitic trimethylol chloride, the amount of which is 5-10 wt% of the oxygen-containing heterocyclic diacyl halide compound. Pyromellitic trimethylol chloride is a trifunctional acyl halide compound, and adding a small amount can increase the strength of the crosslinking network.
[0016] Further, in step S1, the reaction conditions are: stirring at 10~30℃ for 3~6h, solid-liquid separation after the reaction, and drying of the solid at 60~70℃ for 12~24h.
[0017] This invention uses asphalt as a precursor. Under the catalysis of Lewis acids, diacyl halides containing oxygen heterocycles crosslink with asphalt molecules via Friedel-Crafts reactions, thereby introducing oxygen-containing heterocycles and active carbonyl groups into the asphalt molecular framework and constructing a rigid crosslinked framework that restricts long-range rearrangement of aromatic molecules. This rigid crosslinked network plays a steric hindrance role during subsequent high-temperature carbonization, blocking the slippage and parallel stacking of graphene microsheets, forcing the carbon layers to bend and twist, thus introducing a large number of topological defects in situ into the framework and forming amorphous short-range graphite domains with large lattice spacing. Simultaneously, the electron-rich oxygen-containing groups (furan epoxide, carbonyl) introduced after crosslinking can serve as coordination sites, interacting with metal ions (such as Zn) in Lewis acids. 2+ Mg 2+ Al 3+ Fe 3+ Coordination chelation occurs, thereby achieving molecular-level anchoring and uniform distribution of metal ions in the asphalt matrix. Taking ZnCl2 as an example, the anchored zinc-oxygen complex is transformed in situ into uniform nano-ZnO particles during pre-carbonization. Then, during the high-temperature carbonization stage, the nano-ZnO particles are carbothermally reduced to metallic Zn vapor (ZnO + C → Zn↑ + CO). The Zn vapor escapes, leaving initial pores. Under the constraint of the rigid cross-linked framework, the initial pores further shrink and close, forming a closed-pore structure with sodium storage capacity. This vaporization escape mechanism allows for in-situ pore formation in zinc-containing Lewis acid systems without additional acid washing. For other Lewis acids such as AlCl3, MgCl2, and FeCl3, their metal ions can also form nano-oxide templates through coordination anchoring to occupy space, but the vacancies left after acid washing form pores. In addition, during the high-temperature carbonization process, some oxygen atoms in the diacyl halide compounds containing oxygen heterocycles remain in the carbon framework, achieving oxygen heteroatom doping. The synergistic effect of crosslinking, pore formation, and doping provides abundant active sites and unobstructed diffusion channels for the storage and rapid interlayer migration of sodium ions.
[0018] Further, in step S2, the inert atmosphere is nitrogen and / or argon; the pre-carbonization conditions are: holding at 250~400℃ for 1~4h; the high-temperature carbonization conditions are: holding at 1000~1300℃ for 2~5h.
[0019] Furthermore, when the Lewis acid mentioned in step S1 is not a zinc-containing Lewis acid (ZnCl2), step S2 includes an acid washing step after pre-carbonization and before high-temperature carbonization to remove metal ions. The acid washing conditions are as follows: soak the pre-carbonized material in a 1-2M hydrochloric acid solution for 1-3 hours, wash with pure water until neutral, and dry at 80-90℃ for 12-24 hours.
[0020] The present invention also provides an asphalt-based hard carbon material for the negative electrode of a sodium-ion battery, which is prepared by the above-described preparation method.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] This invention uses an oxygen-containing heterocyclic diacyl halide compound as a crosslinking agent. Under the catalysis of a Lewis acid, it undergoes precise molecular-level crosslinking with asphalt molecules via a Friedel-Crafts reaction to form a rigid crosslinked network, thereby inhibiting the melting and rearrangement of aromatic layers at high temperatures. Simultaneously, the coordination of oxygen-containing groups with metal ions in the Lewis acid achieves molecular-level anchoring of metal ions in the asphalt matrix. After pre-carbonization and high-temperature carbonization, a large number of nanoscale closed pores are formed in situ, and oxygen doping is achieved simultaneously. Through the synergistic effect of crosslinking, pore formation, and doping, a hard carbon material with a highly disordered carbon structure, large interlayer spacing, and abundant closed-pore characteristics is obtained. Its sodium storage capacity and initial coulombic efficiency are both improved, and its rate performance is excellent. Attached Figure Description
[0023] Figure 1 The image shows the SEM images of the modified asphalt and the raw asphalt (Pitch) obtained in step S1 of Example 1.
[0024] Figure 2 The Fourier transform infrared spectra of the modified asphalt and the raw asphalt (Pitch) obtained in step S1 of Example 1 are shown.
[0025] Figure 3 The images show the XRD patterns of the hard carbon materials prepared in Example 1 and Comparative Example 1.
[0026] Figure 4 This is a high-resolution transmission electron microscope (HRTEM) image of the hard carbon material prepared in Example 1.
[0027] Figure 5 This is a high-resolution transmission electron microscope (HRTEM) image of the hard carbon material prepared in Comparative Example 1.
[0028] Figure 6The charge-discharge curves at 50 mA / g are for the hard carbon materials prepared in Example 1 and Comparative Example 1. Detailed Implementation
[0029] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.
[0030] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0031] Petroleum asphalt powder was purchased from Xinjiang Xuandong Energy Co., Ltd., with a softening point of approximately 100 ℃ and a particle size of approximately 320 mesh.
[0032] 4H-pyran-2,6-dicarboxylic acid chloride was purchased from Shenzhen Aituo Chemical Co., Ltd.
[0033] Example 1
[0034] S1. The asphalt powder was vacuum dried at 80℃ for 12 hours. 10g of the dried asphalt powder was placed in a three-necked flask, and nitrogen gas was introduced to replace the air in the system three times. Then, 400mL of anhydrous n-heptane was added, and the mixture was stirred at 400rpm for 30 minutes at 20℃ to obtain a mixture. Then, 0.5g of 2,5-furandicarboxylic acid chloride and 0.8g of anhydrous ZnCl2 were added (i.e., the mass ratio of asphalt powder, 2,5-furandicarboxylic acid chloride, and ZnCl2 was 100:5:8), and the mixture was stirred at 20℃ for 4 hours. After the reaction was completed, 40mL of distilled water was added to quench the reaction (uncoordinated free Zn can be removed by washing with water after the reaction). 2+ The zinc oxide complex anchored in the matrix was retained, which proves that Zn 2+ The molecular-level anchoring effect avoids the negative impact of excessive metal residue on sodium storage capacity. After filtration and drying of the solids at 60°C for 12 hours, modified asphalt is obtained.
[0035] S2. The modified asphalt was placed in a tube furnace and heated to 350°C at 5°C / min under an argon atmosphere, and held for 2 hours; then heated to 1100°C at 5°C / min, held for 4 hours, and naturally cooled to room temperature to obtain asphalt-based hard carbon material for sodium-ion battery anodes.
[0036] Example 2
[0037] The rest is the same as in Example 1, except that the amounts of 2,5-furandicarboxylic acid chloride and ZnCl2 are different in step S1. Specifically, 0.8g of 2,5-furandicarboxylic acid chloride and 1.0g of anhydrous ZnCl2 are used, that is, the mass ratio of asphalt powder, 2,5-furandicarboxylic acid chloride and ZnCl2 is 100: 8: 10.
[0038] Example 3
[0039] The rest is the same as in Example 1, except that the amounts of 2,5-furandicarboxylic acid chloride and ZnCl2 are different in step S1. Specifically, 0.8g of 2,5-furandicarboxylic acid chloride and 1.2g of anhydrous ZnCl2 are used, that is, the mass ratio of asphalt powder, 2,5-furandicarboxylic acid chloride and ZnCl2 is 100: 8: 12.
[0040] Example 4
[0041] The rest is the same as in Example 1, except that the amounts of 2,5-furandicarboxylic acid chloride and ZnCl2 are different in step S1. Specifically, 1.0g of 2,5-furandicarboxylic acid chloride and 1.2g of anhydrous ZnCl2 are used, that is, the mass ratio of asphalt powder, 2,5-furandicarboxylic acid chloride and ZnCl2 is 100:10:12.
[0042] Example 5
[0043] The rest is the same as in Example 1, except that in step S1, 4H-pyran-2,6-dicarboxylic acid chloride is used to replace 2,5-furan-dicarboxylic acid chloride by mass.
[0044] Example 6
[0045] The rest is the same as in Example 1, except that: in step S1, aluminum chloride (AlCl3) is used to replace ZnCl2 by mass; in step S2, acid washing is performed after pre-carbonization; specifically:
[0046] S1. The asphalt powder was vacuum dried at 80℃ for 12h. 10g of the dried asphalt powder was placed in a three-necked flask, and nitrogen was introduced to replace the air in the system three times. Then 400mL of anhydrous n-heptane was added, and the mixture was stirred at 400rpm for 30min at 20℃ to obtain a mixture. Then 0.5g of 2,5-furandicarboxylic acid chloride and 0.8g of anhydrous AlCl3 (i.e., the mass ratio of asphalt powder, 2,5-furandicarboxylic acid chloride, and AlCl3 is 100:5:8) were added, and the mixture was stirred at 20℃ for 4h. After the reaction was completed, 40mL of distilled water was added to quench the reaction, and then the mixture was filtered and the solids were dried at 60℃ for 12h to obtain modified asphalt.
[0047] S2. The modified asphalt was placed in a tube furnace and heated to 350°C at 5°C / min under an argon atmosphere, held for 2 hours, and then naturally cooled to room temperature. It was then soaked in 1M hydrochloric acid solution for 2 hours, washed with pure water until neutral, and dried at 80°C for 12 hours to obtain pre-carbonized material. The pre-carbonized material was then placed in a tube furnace again and heated to 1100°C at 5°C / min, held for 4 hours, and then naturally cooled to room temperature to obtain asphalt-based hard carbon material for sodium-ion battery anodes.
[0048] Example 7
[0049] The rest is the same as in Example 1, except that in step S1, pyromellitic methyl chloride is added, and the amount used is 8 wt% of 2,5-furandicarboxylic acid chloride; specifically:
[0050] S1. The asphalt powder was vacuum dried at 80℃ for 12h. 10g of the dried asphalt powder was placed in a three-necked flask, and nitrogen was introduced to replace the air in the system three times. Then 400mL of anhydrous n-heptane was added, and the mixture was stirred at 400rpm for 30min at 20℃ to obtain a mixture. Then 0.463g of 2,5-furandicarboxylic acid chloride, 0.037g of trimesoyl chloride, and 0.8g of anhydrous ZnCl2 were added, and the mixture was stirred at 20℃ for 4h. After the reaction was completed, 40mL of distilled water was added to quench the reaction, and the mixture was then filtered and the solids were dried at 60℃ for 12h to obtain modified asphalt.
[0051] S2, same as Example 1.
[0052] Comparative Example 1
[0053] The rest is the same as in Example 1, except that 2,5-furandicarboxylic acid chloride is not added in step S1; specifically:
[0054] S1. Mix 10g of asphalt powder with 0.8g of ZnCl2 to obtain a mixture;
[0055] S2. The mixture is placed in a tube furnace and heated to 350°C at 5°C / min under an argon atmosphere, and held for 2 hours; then heated to 1100°C at 5°C / min, held for 4 hours, and naturally cooled to room temperature to obtain pitch-based hard carbon material for sodium-ion battery anode.
[0056] Testing and Analysis
[0057] 1. Structural characterization
[0058] a) SEM analysis
[0059] The SEM images of the modified asphalt and the raw material asphalt (Pitch) obtained in step S1 of Example 1 are shown below. Figure 1 As shown, the pitch exhibits a large, relatively smooth, and dense blocky morphology. After crosslinking modification of the asphalt with the addition of 2,5-furandicarboxylic acid chloride, its microstructure underwent a significant topological evolution, with the originally dense blocky structure completely transformed into a highly wrinkled, interconnected, complex network structure. This morphological transformation directly reflects the dramatic reorganization of the internal structure of the asphalt during the modification process, indicating that the introduction of 2,5-furandicarboxylic acid chloride has a significant impact on the arrangement of asphalt molecules.
[0060] b) Fourier transform infrared spectroscopy analysis
[0061] The Fourier transform infrared spectra of the modified asphalt and the raw material asphalt (Pitch) obtained in step S1 of Example 1 are as follows: Figure 2 As shown in the figure, compared with Pitch, the aliphatic -CH2 and -CH3 stretching vibration peaks of the modified asphalt in Example 1 are significantly weakened, while the furan COC vibration peak is enhanced, and typical carbonyl stretching vibration characteristic peaks appear. This indicates that 2,5-furandicarboxylic chloride has successfully undergone deep cross-linking with the aromatic ring system of asphalt via Friedel-Crafts reaction. The changes in Fourier transform infrared spectrum and the aforementioned changes in SEM morphology corroborate each other, jointly indicating that 2,5-furandicarboxylic chloride has successfully initiated a cross-linking reaction between asphalt molecules. This cross-linked network can effectively suppress the rearrangement of graphite domains during subsequent high-temperature carbonization, thereby constructing a rigid carbon skeleton with high structural stability and laying the structural foundation for the formation of closed-pore structures.
[0062] c) XRD analysis
[0063] The XRD patterns of the hard carbon materials prepared in Example 1 and Comparative Example 1 are shown below. Figure 3 As shown in the figure, the (002) diffraction peak of the hard carbon material obtained in Comparative Example 1 (without crosslinking modification) is sharper, indicating a higher degree of ordered stacking of carbon layers and obvious graphitized microcrystals. In contrast, the (002) diffraction peak of the hard carbon material obtained in Example 1 (crosslinked modification with 2,5-furandicarboxylic acid chloride) is significantly broadened and shifted to a lower angle, indicating that the crosslinking network effectively inhibits the melting and rearrangement of aromatic layers at high temperatures, increases the disorder of the carbon material, increases the interlayer spacing, and enhances the disordered layer structure characteristics. This provides a structural prerequisite for the formation of closed pores during subsequent high-temperature carbonization and thus improves the sodium storage capacity of the low-pressure platform.
[0064] d) High-resolution transmission electron microscopy (HRTEM) analysis
[0065] The HRTEM images of the hard carbon materials prepared in Example 1 and Comparative Example 1 are shown below. Figure 4 and Figure 5 As shown in the figure, compared with Comparative Example 1, the hard carbon material prepared in Example 1 has bent and closed local graphite domains. These twisted and folded graphite sheets surround each other, forming a large number of nanoscale closed-pore structures. These closed pores provide favorable conditions for the precipitation of sodium metal clusters inside the hard carbon, thereby effectively contributing to the sodium storage capacity of the low-pressure plateau region. The hard carbon materials of the other examples also have similar HRTEM images to those of Example 1.
[0066] Based on the above analysis, the hard carbon material prepared by the method of the present invention in the embodiments has a highly disordered carbon structure, expanded interlayer spacing, and abundant closed-pore features. These structural characteristics together provide sufficient active sites and diffusion channels for the storage of sodium ions.
[0067] 2. Electrochemical performance testing
[0068] The hard carbon material, conductive additive SP, and binder CMC / SBR obtained in the above examples and comparative examples were mixed at a weight ratio of 93:3:2 and dissolved in water. After stirring, a uniform slurry was obtained. The slurry was then uniformly coated onto carbon-coated aluminum foil using a 50 μm doctor blade, dried, and sliced to obtain the negative electrode sheet. The dried negative electrode sheet was then assembled into a coin cell using a sodium metal negative electrode, a polypropylene separator, and a 1 M NaPF6 EC / DMC / EMC (volume ratio 1:1:1) mixed solution as the electrolyte. The battery was then tested on a LAND test platform. The charge-discharge curves of the hard carbon material obtained in Example 1 and Comparative Example 1 at 50 mA / g are shown below. Figure 6 As shown in Table 1, the electrochemical data of the hard carbon materials prepared in each embodiment and comparative example are summarized in Table 1.
[0069] Table 1 Electrochemical performance
[0070]
[0071] As shown in Table 1, compared with the comparative example, the sodium storage capacity and rate performance of the hard carbon material prepared in the embodiments of the present invention are significantly improved, and the initial coulombic efficiency is also improved. The specific charging capacity at a current density of 50 mA / g is above 350 mAh / g, and at a current density of 200 mA / g, it is above 330 mAh / g; simultaneously, the initial coulombic efficiency at a current density of 50 mA / g is also above 84%. In the preferred embodiments, the specific charging capacity at a current density of 50 mA / g is above 370 mAh / g, and at a current density of 200 mA / g, it is above 350 mAh / g; the initial coulombic efficiency at a current density of 50 mA / g is also above 88%.
[0072] Based on the above structural characterization and electrochemical performance tests, this invention achieves precise molecular-level crosslinking of asphalt molecules and Zn through the synergistic effect of oxygen-containing heterocyclic diacyl halides and Lewis acids. 2+ Through uniform anchoring and in-situ closed-cell construction, a hard carbon material with a highly disordered carbon structure, large interlayer spacing and abundant closed-cell characteristics was successfully prepared, giving it excellent sodium storage performance and good rate performance.
Claims
1. A method for preparing pitch-based hard carbon material for sodium-ion battery negative electrodes, characterized in that, Includes the following steps: S1. Add asphalt powder, oxygen-containing heterocyclic diacyl halide compound, and Lewis acid to an organic solvent, and then stir to react to obtain modified asphalt; S2. Modified asphalt is pre-carbonized and then carbonized at high temperature under an inert atmosphere to obtain asphalt-based hard carbon material for sodium-ion battery anodes.
2. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of the asphalt powder, the oxygen-containing heterocyclic diacyl halide compound, and the Lewis acid is 100:(5~10):(8~12), preferably 100:(5~8):(8~10).
3. The preparation method according to claim 1, characterized in that, In step S1, the asphalt powder is selected from at least one of coal tar pitch, petroleum asphalt, shale asphalt, natural asphalt, and mesophase asphalt, with a softening point of 65~160℃ and a particle size of 200~400 mesh.
4. The preparation method according to claim 1, characterized in that, In step S1, the oxygen-containing heterocyclic diacyl halide compound is selected from at least one of 2,5-furandicarboxylic acid chloride and 4H-pyran-2,6-dicarboxylic acid chloride, preferably 2,5-furandicarboxylic acid chloride.
5. The preparation method according to claim 1, characterized in that, In step S1, the Lewis acid is selected from at least one of aluminum chloride, zinc chloride, magnesium chloride, and ferric chloride; preferably zinc chloride; the solvent is selected from at least one of tetrahydrofuran, N-methylpyrrolidone, carbon tetrachloride, dichloroethane, and n-heptane.
6. The preparation method according to claim 1, characterized in that, In step S1, the reaction raw materials also include pyromellitic trimethylol chloride, the amount of which is 5-10 wt% of the oxygen-containing heterocyclic diacyl halide compound.
7. The preparation method according to claim 1, characterized in that, In step S1, the reaction conditions are: stirring at 10~30℃ for 3~6h, followed by solid-liquid separation and drying of the solid at 60~70℃ for 12~24h after the reaction is completed.
8. The preparation method according to claim 1, characterized in that, In step S2, the inert atmosphere is nitrogen and / or argon; the pre-carbonization conditions are: holding at 250~400℃ for 1~4h; the high-temperature carbonization conditions are: holding at 1000~1300℃ for 2~5h.
9. The preparation method according to claim 1, characterized in that, When the Lewis acid mentioned in step S1 is not a zinc-containing Lewis acid, step S2 includes an acid washing step after pre-carbonization and before high-temperature carbonization. The acid washing conditions are as follows: soak the pre-carbonized material in a 1-2M hydrochloric acid solution for 1-3 hours, wash with pure water until neutral, and dry at 80-90℃ for 12-24 hours.
10. A pitch-based hard carbon material for the negative electrode of a sodium-ion battery, prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Oxidized asphalt-based hard carbon negative electrode material for sodium-ion battery and preparation method of oxidized asphalt-based hard carbon negative electrode material
CN115991467A
Preparation method and application of asphalt-based hard carbon nanosheet
CN116354335A
A phosphorus-sulfur co-doped hard carbon negative electrode material and its preparation method and application
CN119038529B